2005
DOI: 10.1111/j.1469-0691.2004.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of methicillin-resistant Staphylococcus aureus with reduced susceptibility to glycopeptides in Belgian hospitals

Abstract: Staphylococcus aureus strains with decreased susceptibility to glycopeptides (GISA) have been associated with increased risk of glycopeptide treatment failure. To assess the prevalence of these strains in hospitalised patients in Belgium, 455 methicillin-resistant S. aureus (MRSA) isolates collected in 2001 were screened by two assays: (i) growth on vancomycin agar screen (VAS; brain heart infusion agar (BHI) + vancomycin 6 mg/L); and (ii) a synergy/antagonism test with aztreonam/cefazolin on Mu3 agar (BHI + v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
2
16
0
1
Order By: Relevance
“…A study of MRSA isolates from 63 French hospitals found that only 0.7% of isolates were hVISA isolates after screening with BHI agar containing 6 g teicoplanin per ml and confirmation by PAP (37), with similarly low rates found by some other French studies and in Belgium (69,230,271). However, a subsequent study at one French institution, which screened 2,300 S. aureus isolates using BHIA with 4 g teicoplanin per ml, followed by MET and then PAP confirmation, found that 11% of the isolates were hVISA isolates, which were found to be clonal by pulsed-field gel electrophoresis (93).…”
Section: Global Epidemiology and Associated Features Of Hvisa And Visamentioning
confidence: 99%
“…A study of MRSA isolates from 63 French hospitals found that only 0.7% of isolates were hVISA isolates after screening with BHI agar containing 6 g teicoplanin per ml and confirmation by PAP (37), with similarly low rates found by some other French studies and in Belgium (69,230,271). However, a subsequent study at one French institution, which screened 2,300 S. aureus isolates using BHIA with 4 g teicoplanin per ml, followed by MET and then PAP confirmation, found that 11% of the isolates were hVISA isolates, which were found to be clonal by pulsed-field gel electrophoresis (93).…”
Section: Global Epidemiology and Associated Features Of Hvisa And Visamentioning
confidence: 99%
“…The criterion used to define hGISA was any isolate recovered by any screening method with a vPAP-AUC ratio of 0.9 to 1.29 and/or a tPAP with a resistant subpopulation growing at concentrations Ͼ8 mg of teicoplanin/liter (18,29).…”
Section: Resultsmentioning
confidence: 99%
“…Volumes (50 l) were inoculated onto BHI agar plates containing 0, 0. (18,29). After 48 h of incubation at 35°C, the colonies were counted, and the log of the CFU/ml was plotted against the antibiotic concentration by using GraphPad Prism software (GraphPad Software, Inc., San Diego, CA) to obtain vancomycin PAPs (vPAP) and teicoplanin PAPs (tPAP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 9 out of 156 MRSA isolates (5.9%) were identified as hVISA by MET. In USA, Italy, Canada, France, Israel, Belgium and Asia, the prevalence of hVISA in MRSA was 7.5, 2.8, 1.3, 0.21, 6, 0.7 and 4.3% (Rybak et al, 2008;Campanile et al, 2010;Adam et al, 2010;Reverdy et al, 2001;Maor et al, 2007;Nonhoff et al, 2005;Song et al, 2004), respectively. The disparity in the prevalence of hVISA in different areas may be due to the different detection methods, geographical differences and variable incidence.…”
Section: Discussionmentioning
confidence: 99%